Effectiveness of the virtual reality chemical disaster training program in emergency nurses: A quasi experimental study. (December 2022) - Chang, Chih-Wei; Lin, Che-Wei; Huang, Chu-Yu; Hsu, Chin-Wang; Sung, Han-Yu; Cheng, Su-Fen
Abstract: Background: In Taiwan, 50 % of the chemical disasters in the last decade were industrial accidents. The leakage of industrial toxic chemical substances may cause significant environmental pollution and harms. Taiwan's chemical disaster education and training mainly rely on simulation, which is labor-intensive, time-consuming, and costly. Tabletop drills are often used to as a substitute for simulations. However, tabletop drills lack a realistic presence. The 360° virtual reality (VR) transforms knowledge of disaster preparedness into audio-visual and other sensory experiences and allows participants to be physically immersed in an environment. Purpose: This study examined effectiveness of a "360° VR chemical disaster training program" on disaster preparedness and self-efficacy in ER nurses. Method: This study used convenience sampling and quasi-experimental design with two-group repeated measures. Seventy-seven ER nurses were recruited with the experimental group ( n  = 32) receiving chemical disaster training through 360° VR and the control group ( n  = 35) receiving training through tabletop drills. Data were collected before, one week after and three weeks after the intervention. Result: Participants in the experimental group were significantly younger and less experienced in disaster management than those in the control group. There were no between-group differences in the participants' self-assessment of chemical disaster preparedness and self-efficacy before the intervention. The intervention group showed significantly higher self-assessment chemical disaster preparedness scores than the comparison group ( p  < .05) one week after the intervention. However, no significant differences were found three weeks after the intervention. Conclusion: This study found that both 360° VR and tabletop drills improved preparedness and self-efficacy in chemical disasters among ER nurses. VR could be used for disaster preparedness training for nurses without prior disaster response experiences/ drills, whereas tabletop drills were more suitable for nurses with prior experiences. Both methods may effectively promote nurses' learning effectiveness and self-efficacy in chemical disaster preparedness. Highlights: ER nurses need to possess the disaster preparedness core knowledge and skills. Virtual reality (VR) is fit for teaching rare and complicated clinical situations. VR provides realistic immersive experiences to promote learning effectiveness. 360° VR could be used for nurses without prior experiences of managing disasters. Tabletop drills were suitable for nurses with prior disaster response experiences.